By the Horns: Issue #6 (By the Horns, 6,, 2021)
Once upon a time, Elodie fell for a good man named Shintaro. They made a life together filled with adventure, laughter and love. Then one day... it was cruelly ripped away from them. This is their story.

By the Horns: Issue #8 (By the Horns, 8,, 2021)
After nearly a year spent traversing the continent of Solothus, Elodie's revenge mission nears its end. But before she can avenge her husband, she's in for the fight for her life against the tiger fang enchantress, Feng Po, aboard the dreaded Augernaut.

By the Horns: Issue #5 (By the Horns, 5,, 2021)
The abduction of Rigby has taken a heavy toll on Elodie and her allies as they make their way across the continent toward the western stronghold of Qeb, the night sand warlock. In the north, the wind wizards' villainous plan for Solothus intensifies.

By the Horns: Issue #2 (By the Horns, 2,, 2021)
Elodie and Sajen make their way to the island home of Futen, the Dark Demon Sorcerer of the Western Wind, to have a chat about unicorns. Their talk does not go well…

By the Horns: Issue #4 (By the Horns, 4,, 2021)
Elodie and her team lock horns with the volcanic sorcerer, Pazuzunox! Meanwhile, Haru and the villagers of Wayfarer are attacked by the wizard of the western wind, who means to take all their magic by force.

By the Horns: Issue #3 (By the Horns, 3,, 2021)
After defeating the western wind mage, Elodie and Sajen have a new mission. But to track down the other sorcerers they'll need to put their trust in the floating eyeball named Evelyn to guide them across the continent. Plus, Sajen has his work cut out for him if he wants to prevent Elodie from killing their unicorn travel companions, Zoso and Rigby.

By the Horns: Issue #7 (By the Horns, 7,, 2021)
Stranded in the northern tundra of Ataraxy after narrowly escaping death, a weary Elodie and her team travel toward the Arctic Sleep to face the sorceress, Feng Po. But are they already too late to stop her from stealing all the magic on the continent?

By the Horns: Issue #1 (By the Horns, 1,, 2021)
Elodie hates unicorns. For nearly a year, she's dedicated her life to tracking down and killing them all for trampling her husband, Shintaro. Now exiled from her farming village of Wayfarer for selfishly neglecting her duties, Elodie and her half wolf/half deer companion, Sajen, search the continent of Solothus for clues to the whereabouts of unicorns. When they discover a lead in the port city of Lycus, their revenge mission suddenly takes a dangerous turn.

By the Horns: Issues #1-8 (By the Horns, 1,, 2022)
By The Horns is an epic, sci-fi fantasy comic book series set in a dangerous world of magic and technology written by Markisan Naso, illustrated by Jason Muhr and colored by Andrei Tabacaru, published monthly by Scout Comics. Elodie hates unicorns. For nearly a year, she's dedicated her life to killing them all for trampling her husband. Exiled from her village home for selfishly neglecting her duties, Elodie and her companion, Sajen, search the continent of Solothus to exact bloody revenge. But to make unicorns extinct she'll need to fake an alliance with Zoso and Rigby, two of the very beasts she hates most, and battle four wind sorcerers who are extracting magic from all the mystical creatures on the continent. With the ability to rip off the unicorn horns and combine them to form wizard-slaying weapons, Elodie has a fighting chance. But will she decide to use those gifts to save magic in the world? Or destroy all the unicorns left alive?

The wind rises (By the horns, 1,, 2022)
Description Not Provided